Meristem Culture Method for Virus Elimination from Shallot Bulb - Prabawati Hyunita Putri; Diny Dinarti; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2020)
Meristem Culture Method for Virus Elimination from Shallot Bulb Shallot farmers in Indonesia have commonly grown bulbs from the previous planting season as seed sources for the next season. This may cause the accumulation of viruses in bulbs which in turn lowering plant productivity. A research was conducted to optimize the meristem culture method combined with thermotherapy (30 ºC) to produce virus-free shallot bulbs. Shallot bulbs of cv. Bima Curut that had been confirmed infected by Potyvirus and Carlavirus were used as explant sources. Bulb sterilization was carried out using bactericides, fungicides, and sodium hypochlorite. Meristem shoots of 0.6 to 0.7 mm in size were isolated from bulbs and plant successively in the shoot, root, and bulb induction medium to form mini bulbs. The mini bulbs were then planted in the screen house for 2 to 2.5 months until micro bulbs were formed. Virus detection by reverse transcription-polymerase chain reaction method confirmed that plantlets at the multiplication stage and plants in the screen house were free of Potyvirus and Carlavirus infestations. This study showed that the meristem culture method combined with thermotherapy is a potential approach for producing virus-free shallot bulbs.